Enhancing Pelargonium graveolens L’Hér. (geranium) growth using Zn–Al and Mg–Al LDH nanomaterials: a biochemical approach - Shimaa Hashem; Fatma Mohamed; Momtaz M. Hegab; Mohammad K. Okla; Amal Mohamed AlGarawi; Hamada AbdElgawad; Mona Sayed (Chemical and Biological Technologies in Agriculture)
Abstract The approaches of nanoparticles (NPs) usage have been successfully applied to increase the growth and biological activity of aromatic and medicinal plants. In this context, we studied the effects of zinc–aluminum layered double hydroxide (Zn–Al LDH) and magnesium–Al LDH (Mg–Al LDH) NPs on geranium plants. Both LDH NPs were synthesized using the co-precipitation technique and characterized with SEM, FTIR, XRD, and Zeta potential. Using the spray method, Zn–Al LDH and Mg–Al LDH NPs (10 ppm) were used in a factorial experiment with a fully randomized design. Applying LDH NPs increased Mg and Zn content, which boosted plant growth, photosynthetic pigments, and soluble sugar levels. The administration of both LDH NPs results in a constant increase in secondary metabolites such as essential oils (EOs). Monoterpenes such as geraniol (32.7%) and β-citronellol (29.18%) were found to be the main components of the EO. Geranium plants treated with Mg–Al LDH NPs exhibited the highest levels of polyphenols (44.5%), flavonoids (33.5%), and total antioxidant capacity (31.7%). Additionally, LDH NPs had a favorable effect on antioxidant enzyme activity including catalase and peroxidase activities. Overall, Zn–Al LDH and Mg–Al LDH NPs foliar application acted as an elicitor to enhance growth and bioactive metabolite accumulation in geranium plants. Despite these promising results, several challenges remain for the broader application of LDH NPs in agriculture. Graphical abstract